Minocycline attenuates oxycodone-induced positive subjective responses in non-dependent, recreational opioid users - Mogali, S.; Askalsky, P.; Madera, G.; Jones, J.D.; Comer, S.D. (Pharmacology, biochemistry and behavior, 2021)
Recent data suggest that glial cells may be involved in the analgesic effects and abuse liability of opioids. Preclinical studies have demonstrated that mu-opioid-receptor-selective agonists, such as oxycodone, activate glia and increase the release of cytokines, causing a suppression of opioid-induced analgesic effects. Preclinical studies also show that certain medications, such as the broad-spectrum tetracycline antibiotic minocycline, inhibit opioid-induced glial activation and thereby enhance the analgesic effects of opioids. Importantly, minocycline reduces the rewarding effects of opioids at the same doses that it enhances opioid-induced analgesia. The purpose of the present study was to assess the effects of acute administration of minocycline on the subjective, physiological, and analgesic effects of oxycodone in human research volunteers. This study was a within-subject, randomized, double-blind outpatient study. Participants completed five separate sessions in which they received 0, 100, or 200 mg minocycline (MINO) simultaneously with either 0 or 40 mg oxycodone (OXY). The subjective, physiological, and analgesic effects of OXY were measured before and repeatedly after drug administration. Participants were between 21 and 45 years of age, non-treatment seeking, non-dependent recreational opioid users (N = 12). This study was conducted between 2013 and 2014 at the New York State Psychiatric Institute in New York, NY. MINO 100 and 200 mg were safe and well-tolerated in combination with OXY 40 mg. MINO 200 mg administered with OXY 40 mg attenuated OXY-induced positive subjective effects such as “Good Effect” and “Liking” compared to OXY alone. MINO did not alter the physiological or analgesic effects of OXY. MINO may attenuate the abuse liability of mu-opioid-receptor-selective agonists. •Microglial inhibitors, such as minocycline (MINO), may be involved in attenuating the abuse liability of oral oxycodone (OXY).•Oral MINO 100 mg and 200 mg was safe and well-tolerated in combination with oral OXY 40 mg.•MINO attenuated OXY-induced positive subjective effects compared to OXY alone.•MINO did not alter physiologic or analgesic effects of OXY.